PENGGUNAAN VIDEO PEMBELAJARAN BERBASIS YOUTUBE UNTUK MENINGKATKAN HASIL BELAJAR BILANGAN PECAHAN SECARA DARING - Luh Widyastuti (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
From the background of global conditions regarding the outbreak of covid-19 which causes low student learning outcomes and student interest in mathematics lessons because learning is carried out online, this study aims to improve student learning outcomes and interest in mathematics lessons about fractions through video-based learning media YouTube. This research is a classroom action research conducted in two cycles with the research subjects being 47 students of class VI SDN 1 Peguyangan. Collecting data in this study using test instruments and questionnaires with quantitative data collection which is processed into qualitative data. Regarding the data on student learning outcomes seen from the initial conditions with the pretest to the first cycle there has been an increase, as well as in the second cycle. When compared with the PAP criteria, learning outcomes have increased from the initial conditions in the low category to being in the moderate category after the first cycle and remaining in the moderate category after the second cycle. Thus, it can be concluded that the use of YouTube-based learning video media can improve mathematics learning outcomes in class VI SDN 1 Peguyangan online